Mapping and quantification of crop livestock interventions in Africa Rising sites of Ethiopian highlands - Mulugeta, M. (Dilla University, 2017)
Agriculture is the backbone of the Ethiopian economy and therefore this particular sector determines the growth of all the other sectors and, consequently, the whole national economy. The agricultural sector contributes 42% to the country’s GDP, on average, crop production makes up 60% of the sector’s outputs whereas livestock accounts for 27% and other areas contribute 13% of the total agricultural value added (CSA, 2015). The sector is dominated by small-scale farmers who practice rain-fed mixed farming by employing traditional technology, adopting a low input and low output production system. RD&E in smallholder agriculture often focuses on specific elements of the farming system, sometimes leading to the introduction of improved agricultural technologies. There has been a plenty of efforts to achieve sustainable intensification in agricultural production, but many efforts fail to map the dissemination of the crop-livestock interventions, to quantify the inputs saved and the extra amount of outputs obtained by the use of improved technologies and to identify the factors affecting the dissemination of the crop-livestock intervention. As a result, this study was conducted with the objectives of mapping the dissemination of the crop-livestock interventions, quantification of the inputs saved and extra outputs obtained and identification of the factors affecting the dissemination. The study was conducted in the eight kebeles of four districts; Lemo from Hadiya Zone, South region; Sinana from Bale Zone, Oromia region; Basona Worena from North Shewa Zone, Amhara region and Endamehoni from South Tigray Zone, Tigray region. In order to generate relevant data, 160 farm households who were participating in the Africa RISING project were selected using multistage sampling technique. This study also showed that potato (ware and seed) varieties introduced by the project propagated within and outside of the intervention locations. Farmers liked potato for its adaptability and high productivity in all four locations. The duality of the function (food and income) of the potato for the smallholders households make it the most disseminating crop across all sites. Potato yield on average was 16 tons per hectare where as the existing national average was 10 tons per hectare. An average yield of wheat was 21.5 quintals per hectare, average barley yield was 13 quintals and average faba bean yield was 14 quintals per hectare. In terms of profitability potato could fetch on average 62713 birr per hectare when the market price is high, but due to the perishability of the potato and market fluctuation, the net return is not consistent. Faba bean returns about 25866 birr per hectare and wheat returns 10187 birr per hectare whereas barley returns on average 3361 birr per hectare. The most important factors affecting the dissemination of the crop-livestock interventions in the study areas are: education level of the farmers in schooling years, technology characteristics of the interventions, farmers’ perception about the yield, and time after the intervention, extension contact and communication channels. Hence, the future crop livestock interventions seeking to achieve sustainable intensification should carefully consider and choose improved agricultural technologies suitable for the particular agro-ecologies and should give due attention for the factors that affect the dissemination of the crop-livestock technologies.